Bisphenyl-Polymer/Carbon-Fiber-Reinforced Composite Compared to Titanium Alloy Bone Implant - Richard C. Petersen (International Journal of Polymer Science)
Aerospace/aeronautical thermoset bisphenyl-polymer/carbon-fiber-reinforced composites are considered as new advanced materials to replace metal bone implants. In addition to well-recognized nonpolar chemistry with related bisphenol-polymer estrogenic factors, carbon-fiber-reinforced composites can offer densities and electrical conductivity/resistivity properties close to bone with strengths much higher than metals on a per-weight basis. In vivo bone-marrow tests with Sprague-Dawley rats revealed far-reaching significant osseoconductivity increases from bisphenyl-polymer/carbon-fiber composites when compared to state-of-the-art titanium-6-4 alloy controls. Midtibial percent bone area measured from the implant surface increased when comparing the titanium alloy to the polymer composite from 10.5% to 41.6% at 0.8 mm, P<10−4, and 19.3% to 77.7% at 0.1 mm, P<10−8. Carbon-fiber fragments planned to occur in the test designs, instead of producing an inflammation, stimulated bone formation and increased bone integration to the implant. In addition, low-thermal polymer processing allows incorporation of minerals and pharmaceuticals for future major tissue-engineering potential.